Miniature High Gain Slot-Fed Rectangular Dielectric Resonator Antenna For IoT RF Energy Harvesting - A Masius, Alphonsos; Wong, Yan Chiew; Lau, Kok Tee (Elsevier GmbH, 2017)
Radio-frequency (RF) energy harvesting is a promising candidate for alternative power source that can reduce the dependencies on batteries. However, its power density is very low which makes it crucial to have a high gain antenna to increase the power received by the system. This study presents the design of miniature high gain dielectric resonator antenna for RF energy harvesting application with high figure of merit to increase the power received. Numerical approximation is used to assist the antenna design and modelling. The design focused on three parameters which are the width, length, and height of the dielectric resonator. The performance, electric field density, and the radiation patterns of the dielectric resonator antenna have been observed by varying the design parameters. The effect of air gap to the performance is investigated and it is found that 8.11–13% gain improvement and up to 36% improvement in impedance matching is achieved through incorporating thin air gap between the dielectric resonator. Soda-lime glass with relative permittivity 7.75 is used which allows miniaturization and transparency. Experimental results show reasonable agreement to the simulations. The work shows highest antenna gain with smallest size with high FOM at 5 GHz ISM band compared to previous works.